2012
DOI: 10.1200/jco.2011.39.4411
|View full text |Cite
|
Sign up to set email alerts
|

Social Influences on Clinical Outcomes of Patients With Ovarian Cancer

Abstract: A B S T R A C T PurposePrevious research has demonstrated relationships of social support with disease-related biomarkers in patients with ovarian cancer. However, the clinical relevance of these findings to patient outcomes has not been established. This prospective study examined how social support relates to long-term survival among consecutive patients with ovarian cancer. We focused on two types of social support: social attachment, a type of emotional social support reflecting connections with others, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
6
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 51 publications
2
126
6
6
Order By: Relevance
“…While there is some evidence to support a relationship between negative emotional responses, unfavorable coping styles, optimism, depression and social support with cancer recurrence and survival [7,[15][16][17][18][19][20][21], results are inconsistent. Interpreting many of these studies is difficult as they fail to effectively control for prognostic factors and do not adequately consider potential interactions between psychosocial and disease or treatment variables over time.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…While there is some evidence to support a relationship between negative emotional responses, unfavorable coping styles, optimism, depression and social support with cancer recurrence and survival [7,[15][16][17][18][19][20][21], results are inconsistent. Interpreting many of these studies is difficult as they fail to effectively control for prognostic factors and do not adequately consider potential interactions between psychosocial and disease or treatment variables over time.…”
Section: Introductionmentioning
confidence: 79%
“…found that perceived social support was correlated with disease related biomarkers, including NK cell activity [26] and interleukin-6 [27] in women with ovarian cancer. This group have directly linked social support and survival in ovarian cancer, specifying a particular aspect of social support, lower social attachment pre-surgery, predicting shorter survival in 168 women controlling for disease characteristics [21]. Depression and practical social support were not related to survival, while other coping factors were not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that providing different supportive activities through social networks may be able to increase survival rate and decrease mortality, disabilities and recurrence in cancer patients (Vogt et al, 1992;Kroenke et al, 2006;Lutgendorf et al, 2012).…”
Section: Online Social Network Advantages In Cancer Patient Carementioning
confidence: 99%
“…Among individuals with a variety of chronic diseases (e.g., cancer, diabetes, coronary heart disease), social relationships, interpersonal interactions, and social support have been identified as some of the most important predictors of patients' health behaviors (Schiøtz et al 2012), mental health (Mehnert et al 2010), quality of life (Kim et al 2012), disease progression (Barth et al 2010), and survival time (Lutgendorf et al 2012). These findings suggest that interpersonal relationships can influence health outcomes by mitigating or exacerbating the negative effects of stress.…”
Section: Interpersonal Contextsmentioning
confidence: 99%